Cerebellar and basal ganglia inputs define three main nuclei in the mouse ventral motor thalamus - Carmen Alonso-Martínez; Mario Rubio-Teves; Diana Casas-Torremocha; César Porrero; Francisco Clascá (Frontiers Media S.A., 2023)
The thalamus is a central link between cortical and subcortical brain motor systems. Axons from the deep nuclei of the cerebellum (DCN), or the output nuclei of the basal ganglia system (substantia nigra reticulata, SNr; and internal pallidum GPi/ENT) monosynaptically innervate the thalamus, prominently some nuclei of the ventral nuclear group. In turn, axons from these ventral nuclei innervate the motor and premotor areas of the cortex, where their input is critical for planning, execution and learning of rapid and precise movements. Mice have in recent years become a widely used model in motor system research. However, information on the distribution of cerebellar and basal ganglia inputs in the rodent thalamus remains poorly defined. Here, we mapped the distribution of inputs from DCN, SNr, and GPi/ENT to the ventral nuclei of the mouse thalamus. Immunolabeling for glutamatergic and GABAergic neurotransmission markers delineated two distinct main territories, characterized each by the presence of large vesicular glutamate transporter type 2 (vGLUT2) puncta or vesicular GABA transporter (vGAT) puncta. Anterograde labeling of axons from DCN revealed that they reach virtually all parts of the ventral nuclei, albeit its axonal varicosities (putative boutons) in the vGAT-rich sector are consistently smaller than those in the vGLUT2-rich sector. In contrast, the SNr axons innervate the whole vGAT-rich sector, but not the vGLUT2-rich sector. The GPi/ENT axons were found to innervate only a small zone of the vGAT-rich sector which is also targeted by the other two input systems. Because inputs fundamentally define thalamic cell functioning, we propose a new delineation of the mouse ventral motor nuclei that is consistent with the distribution of DCN, SNr and GPi/ENT inputs and resembles the general layout of the ventral motor nuclei in primates.